A kind of high heat-resistant water-based adhesive and preparation method thereof

By using modified graphene oxide and bio-based phthalene resin in aqueous binders, combined with thiol end-group hyperbranched polymers, the problem of decomposition of water-based binders and easy agglomeration of graphene oxide at high temperatures is solved, and high heat resistance and mechanical properties are improved.

CN119307212BActive Publication Date: 2025-03-28ANQING HUALAN TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411858114.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The aqueous binder fails to decompose at high temperatures, and graphene oxide is prone to agglomeration and precipitation, affecting its heat resistance.

Method used

A high-heat-resistant aqueous binder consisting of aqueous epoxy resin, high-temperature resistant additives (composed of modified graphene oxide, hydroxylated cellulose nanofibers and bio-based phthalnitrile resin), thiol-terminated hyperbranched polymers, etc., is used to improve the heat resistance of the binder by modifying the layered structure of graphene oxide and adhesion of bio-based phthalnitrile resin.

Benefits of technology

It significantly improves the high temperature resistance and mechanical properties of water-based binders, avoids the agglomeration and brittleness of graphene oxide, and enhances its stability and strength at high temperatures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of water-based binders, and discloses a high heat-resistant water-based binder and a preparation method thereof, comprising the following raw materials in parts by mass: 40-60 parts of water-based epoxy resin, 15-20 parts of high temperature resistant additives, 10-15 parts of thiol-terminated hyperbranched polymers, 1-2 parts of film formers, 0.5-1 parts of dispersants, 1.5-2 parts of defoamers, 3-4.5 parts of curing agents, and 12-30 parts of deionized water. Kaolin in the powdered material can react with sodium silicate and phosphate, can form Al-O-Si three-dimensional skeletons and heat-resistant aluminum phosphates in the water-based binder, and has high high temperature resistance; the formed Al-O-Si three-dimensional skeletons and heat-resistant aluminum phosphates are coated on the surface of graphene to improve the impact resistance of graphene nanosheets; the thiol-terminated hyperbranched polyester can expand the free volume of water-based epoxy resin, which is beneficial to the movement of epoxy resin molecular chains and improves toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-based adhesives, in particular to a highly heat-resistant water-based adhesive and a preparation method thereof. Background Art

[0002] Water-based adhesives are environmentally friendly adhesives made from natural polymers or synthetic polymers and water as solvent or dispersant to replace toxic organic solvents that pollute the environment. Existing water-based adhesives are not 100% solvent-free and may contain limited volatile organic compounds as additives for their aqueous media to control viscosity or fluidity. They are non-toxic, pollution-free, non-flammable, safe to use, and easy to implement clean production processes. They have high application prospects in the bonding process of automotive interior parts, such as control panels, door panels, ceilings, etc., and in battery manufacturing, they can improve the electrochemical performance and stability of batteries, and have the advantages of environmental protection and corrosion resistance.

[0003] The side chains of the polymer molecular chains of the water-based adhesive matrix contain non-rigid groups with poor heat resistance, such as relatively weak groups such as methyl. Therefore, when the heating temperature is too high, the related chemical bonds will be destroyed, causing the weaker groups to break, affecting the adhesion performance; the layered structure of graphene oxide has good thermal stability and can enhance the heat resistance of water-based adhesives, but graphene oxide is easy to agglomerate and precipitate, and the layered structure is easily destroyed under the action of external forces, affecting the heat resistance of the water-based adhesive. Summary of the invention

[0004] The invention provides a highly heat-resistant water-based binder and a preparation method thereof, which solve the problems of decomposition failure of the water-based binder at high temperature and easy migration and precipitation of graphene oxide.

[0005] The technical solution of the present invention:

[0006] A highly heat-resistant water-based adhesive comprises the following raw materials in parts by weight: 40-60 parts of a water-based epoxy resin, 15-20 parts of a high-temperature-resistant additive, 10-15 parts of a thiol-terminated hyperbranched polymer, 1-2 parts of a film-forming agent, 0.5-1 parts of a dispersant, 1.5-2 parts of a defoaming agent, 3-4.5 parts of a curing agent, and 12-30 parts of deionized water.

[0007] The high temperature resistant additive is obtained by mixing a phthalonitrile resin mixture, hydroxylated cellulose nanofibers, and a coupling agent;

[0008] The phthalonitrile resin mixture is obtained by reacting 4-nitrophthalonitrile with cardanol and then mixing with modified graphene oxide;

[0009] The modified graphene oxide is obtained by mixing and grinding kaolin, sodium silicate, phosphate and starch, and then depositing them on the surface of the graphene oxide;

[0010] The thiol-terminated hyperbranched polymer is obtained by reacting 3-mercaptopropionic acid with a hydroxyl-functionalized hyperbranched polymer.

[0011] Furthermore, a method for preparing a highly heat-resistant water-based adhesive comprises the following steps:

[0012] S1. Mix 2 / 3 parts of deionized water, dispersant, defoamer and curing agent, add film-forming agent, and stir at 800-1200 rpm for 10-20 min to obtain a mixture;

[0013] S2. Mix the mixture, water-based epoxy resin, high temperature resistant additive, thiol-terminated hyperbranched polymer and remaining deionized water, and continue stirring at 1000-1200 rpm for 5-10 minutes to obtain a water-based binder.

[0014] Furthermore, the epoxy equivalent of the waterborne epoxy resin is 800-1400.

[0015] Furthermore, the defoaming agent is at least one of BYK022, BYK057, BYK065, and BYK1765.

[0016] Furthermore, the dispersant is at least one of BYK104 and BYK111.

[0017] Furthermore, the film-forming agent includes any one of benzyl alcohol, phenylethyl alcohol, dodecyl alcohol ester, hexadecanol ester, ethylene glycol butyl ether, ethylene glycol butyl ether acetate, and butylene glycol butyl ether acetate.

[0018] Furthermore, the curing agent is selected from any one of phenolic amine, diethylenetriamine, isophoronediamine, and N-cyanoethyldiethylenetriamine.

[0019] Furthermore, the high temperature resistant additive is specifically prepared by the following steps:

[0020] A1. Mix kaolin, sodium silicate, phosphate and starch, add to deionized water, stir evenly, dry in an oven at 160-180° C. for 0.5-1.5 hours, grind into powder in a grinder, sieve to obtain a composite powder;

[0021] A2, adding graphene oxide to deionized water, ultrasonically treating, adding Tris-HCl with a pH of 7-8, stirring evenly, adding dopamine, stirring and polymerizing in a water bath at 55-65°C for 23-25 ​​hours, adding composite powder, stirring, filtering, washing, and drying to obtain modified graphene oxide;

[0022] A3, adding cardanol, 4-nitrophthalonitrile and potassium carbonate to dimethyl sulfoxide, stirring at 180-220 rpm for 2-3 hours at 20-30 ° C, placing in deionized water, stirring, standing and stratifying, collecting the upper liquid, repeating the operation of placing in deionized water, stirring, standing and stratifying and collecting the upper liquid for 3 times, and drying to obtain a bio-based phthalonitrile resin;

[0023] A4, adding bio-based phthalonitrile resin and modified graphene oxide to ethanol, stirring evenly, drying to remove ethanol, heating to 230-250° C., pre-curing for 1-3 hours, hot pressing, and cooling to room temperature to obtain a phthalonitrile resin mixture;

[0024] A5. Add hydroxylated cellulose nanofibers to deionized water, stir evenly to obtain a dispersion, mix the dispersion and the coupling agent, stir evenly, add acetic acid to adjust the pH value to 3.5-4.5, add the phthalonitrile resin mixture, stir to form a gel, and freeze-dry the gel to obtain a high temperature resistant additive.

[0025] Furthermore, during the above reaction A1, kaolin, sodium silicate, phosphate, starch and deionized water are mixed to form a mixture. Starch can adhere kaolin, sodium silicate and phosphate to form a main structure, which is dried at 160-180° C. for 1 hour and ground to form a composite powder.

[0026] Furthermore, during the above-mentioned A2 reaction process, dopamine is chemically bonded to the functional groups contained on the surface of graphene oxide, so that dopamine acts on the surface of graphene oxide, and dopamine has self-polymerization ability, and can self-polymerize on the surface of graphene oxide to form a polydopamine layer, which has excellent adhesion and can adhere the composite powder to the graphene surface to form modified graphene oxide.

[0027] Furthermore, in the above-mentioned A3 reaction process, the nitric acid group of 4-nitrophthalonitrile can undergo a nucleophilic substitution reaction with a hydroxyl group in cardanol to form a bio-based phthalonitrile resin, which contains a long aliphatic chain with high toughness, and cardanol replaces petroleum-based phenol, which has environmental benefits.

[0028] Furthermore, during the above-mentioned reaction A4, the polar acetonitrile bonds contained in the bio-based phthalonitrile resin can be chemically bonded to the hydroxyl groups in kaolin and sodium silicate on the surface of the modified graphene oxide, so that the flexible long aliphatic chains contained in the cardanol in the bio-based phthalonitrile resin can be embedded in the interlayer of the modified graphene oxide to form a phthalonitrile resin mixture.

[0029] Furthermore, in the above-mentioned A5 reaction process, the hydroxyl groups on the surface of the hydroxylated cellulose nanofibers can be chemically bonded to the hydroxyl groups produced by the hydrolysis of the coupling agent 1,2-bis(trimethoxysilyl)ethane, and the hydroxylated cellulose nanofibers are entangled with each other to form a three-dimensional network structure aerogel, and the polar groups contained on the surface of the phthalonitrile resin mixture can be chemically bonded to the hydroxyl groups in the three-dimensional network structure, so that the phthalonitrile resin mixture is embedded in the three-dimensional network structure aerogel to form a composite aerogel, that is, a high temperature resistant additive.

[0030] Furthermore, in step A1, the usage ratio of kaolin, sodium silicate, phosphate, starch and deionized water is (2-4) g: (0.5-0.7) g: (0.1-0.3) g: (2-3) g: (15-25) mL.

[0031] Furthermore, in step A2, the amount ratio of graphene oxide, deionized water, Tris-HCl, dopamine, and composite powder is (0.1-0.3) g: (180-220) mL: (0.02-0.04) g: (0.3-0.5) g: (0.3-0.7) g.

[0032] Furthermore, in step A3, the amount ratio of the cardanol, 4-nitrophthalonitrile, potassium carbonate, dimethyl sulfoxide, and deionized water is (5-7) g: (3-4) g: (3.2-3.4) g: (10-14) g: (25-35) mL.

[0033] Furthermore, in step A4, the ratio of the bio-based phthalonitrile resin, modified graphene oxide, and ethanol is (3-4) g: (0.3-0.7) g: (25-35) mL.

[0034] Furthermore, in step A5, the ratio of the hydroxylated cellulose nanofibers to deionized water is (0.5-1.5) g: (80-120) mL.

[0035] Further, the thiol-terminated hyperbranched polymer is specifically prepared by the following steps:

[0036] 13.5 g of a hydroxyl-terminated hyperbranched polymer, 3.5 g of 3-mercaptopropionic acid, 0.3 g of p-toluenesulfonic acid and 40 mL of toluene were mixed and reacted at 120° C. for 12 h. After toluene was removed under reduced pressure, a thiol-terminated hyperbranched polymer was obtained.

[0037] Furthermore, in the above reaction process, a catalyst p-toluenesulfonic acid is added to the organic solvent toluene, so that some hydroxyl groups of the hydroxyl-terminated hyperbranched polymer undergo esterification reaction with the carboxyl group of 3-mercaptopropionic acid, 3-mercaptopropionic acid is grafted onto the end of the hyperbranched polymer, a reactive functional group thiol is introduced, and the reaction rate of the hyperbranched polymer and the epoxy resin is increased.

[0038] Furthermore, the amount ratio of the hydroxyl-terminated hyperbranched polymer, 3-mercaptopropionic acid, p-toluenesulfonic acid, and toluene is (13-14) g: (3-4) g: (0.2-0.4) g: (35-45) mL.

[0039] Furthermore, the coupling agent is selected from 1,2-bis(trimethoxysilyl)ethane.

[0040] The present invention has the following beneficial effects:

[0041] (1) In the technical scheme of the present invention, kaolin, sodium silicate and phosphate form a composite powder. When the composite powder is above 600°C, the kaolin in the powdered material can react with sodium silicate and phosphate to form an Al-O-Si three-dimensional skeleton and heat-resistant aluminum phosphate in the aqueous binder, which has high high temperature resistance, thereby improving the high temperature strength of the adhesive; self-polymerize on the surface of graphene oxide to form a polydopamine layer, reduce the number of oxygen-containing functional groups on the surface of graphene oxide, and restore the layered structure of graphene oxide. Its layered structure has good thermal stability, and polydopamine has excellent adhesion, which can adhere the composite powder to the surface of graphene. At high temperature, the composite powder forms an Al-O-Si three-dimensional skeleton and heat-resistant aluminum phosphate coated on the surface of graphene. Its three-dimensional skeleton structure can improve the impact resistance of graphene nanosheets and avoid the decline of heat resistance and mechanical properties caused by the brittleness of graphene.

[0042] (2) In the technical scheme of the present invention, the nitric acid group of 4-nitrophthalonitrile can undergo a nucleophilic substitution reaction with a hydroxyl group in cardanol to form a bio-based phthalonitrile resin, which contains a long aliphatic chain with high toughness, and cardanol replaces petroleum-based phenol, which has environmental benefits; the polar acetonitrile bond contained in the bio-based phthalonitrile resin can be combined with the hydroxyl groups in kaolin and sodium silicate on the surface of modified graphene oxide through chemical bonds, so that the flexible long aliphatic chain contained in cardanol in the bio-based phthalonitrile resin can be embedded in the interlayer of modified graphene oxide, thereby achieving the attachment of the bio-based phthalonitrile resin to the surface of modified graphene oxide, improving the dispersibility of modified graphene oxide, avoiding agglomeration, and improving the heat resistance of the water-based binder.

[0043] (3) In the technical solution of the present invention, a phthalonitrile resin mixture, hydroxylated cellulose nanofibers, and a coupling agent are mixed so that the phthalonitrile resin mixture is embedded in a three-dimensional network structure aerogel. The phthalonitrile resin mixture serves as a supporting skeleton of the hydroxylated cellulose nanofiber aerogel and increases the crosslinking density of the aerogel, thereby avoiding the poor strength of the cellulose skeleton and the lack of strong interfacial force. The cellulose skeleton is easily collapsed when subjected to external force, resulting in the compression of the pores and reducing the flexibility and heat resistance of the aerogel. In addition, the cellulose aerogel has good compatibility with the aqueous binder matrix, so that the aerogel, i.e., the high temperature resistant additive, can better act in the aqueous binder and enhance the heat resistance and toughness of the aqueous binder.

[0044] (4) In the technical scheme of the present invention, 3-mercaptopropionic acid is grafted onto the end of the hyperbranched polymer to introduce a reactive functional group thiol, thereby increasing the reaction rate of the thiol-terminated hyperbranched polymer and the epoxy resin and reducing the curing time of the epoxy resin binder. The functional groups contained in the thiol-terminated hyperbranched polymer have excellent adhesion properties and can also enhance the peel strength. The thiol-terminated hyperbranched polyester can expand the free volume of the water-based epoxy resin, which is beneficial to the movement of the epoxy resin molecular chain and improves the toughness. In addition, the thiol-terminated hyperbranched polymer can be combined with the functional groups contained in the hydroxylated cellulose nanofibers in the high-temperature resistant additive through covalent bonds, so that the high-temperature resistant additive is dispersed in the water-based epoxy resin matrix under the action of the thiol-terminated hyperbranched polymer, thereby increasing the crosslinking density of the water-based epoxy resin and improving the mechanical properties. DETAILED DESCRIPTION

[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] The raw materials used in the embodiments of the present invention are as follows:

[0047] The epoxy equivalent of waterborne epoxy resin is 800-1400, brand E311, Xiamen Aikema Chemical Co., Ltd.

[0048] Graphene oxide: particle size is 2-5μm, Hepfer New Materials Co., Ltd.

[0049] Hydroxylated cellulose nanofibers: Guilin Qihong Technology Co., Ltd.

[0050] Cardanol: CAS: 501-26-8, purchased from Wuhan Lanai Pharmaceutical Chemical Co., Ltd.

[0051] The hydroxyl-terminated hyperbranched polymer is specifically prepared by the following steps:

[0052] 0.1 mol of diethanolamine and 10 mL of methanol were added to a 250 mL three-necked flask. After stirring at room temperature until the diethanolamine was completely dissolved, 0.2 mol of methyl acrylate was slowly added dropwise. The temperature was raised to 35 °C and the reaction was kept at this temperature for 4 hours. Then, the methanol and excess methyl acrylate were removed by vacuum to obtain a hydroxyl-terminated hyperbranched polymer.

[0053] Example 1

[0054] A highly heat-resistant water-based adhesive comprises the following raw materials in parts by weight: 40 parts of water-based epoxy resin, 15 parts of high-temperature resistant additives, 10 parts of thiol-terminated hyperbranched polymers, 1 part of benzyl alcohol, 0.5 parts of BYK104, 1.5 parts of BYK022, 3 parts of phenalkamine, and 12 parts of deionized water.

[0055] A method for preparing a highly heat-resistant water-based adhesive comprises the following steps:

[0056] S1. Mix 2 / 3 parts of deionized water, BYK104, BYK022, and phenalkamine, add benzyl alcohol, and stir at 800 rpm for 10 min to obtain a mixture;

[0057] S2. Mix the mixture, water-based epoxy resin, high temperature resistant additive, thiol-terminated hyperbranched polymer and remaining deionized water, and continue stirring at 1000 rpm for 5 minutes to obtain a water-based binder.

[0058] The high temperature resistant additive is specifically prepared by the following steps:

[0059] A1. Mix 2 g of kaolin, 0.5 g of sodium silicate, 0.1 g of phosphate and 2 g of starch, add to 25 mL of deionized water, stir evenly, dry in an oven at 160 ° C for 0.5 hour, grind to powder in a grinder, and pass through an 800 mesh sieve to obtain a composite powder;

[0060] A2, 0.1g of graphene oxide was added to 200mL of deionized water, and ultrasonic treatment was performed at 40kHz for 60min, 0.03g of Tris-HCl with a pH of 7 was added, and the mixture was stirred evenly, 0.4g of dopamine was added, and the mixture was stirred and polymerized in a water bath at 60°C for 23-25 ​​hours, 0.5g of the composite powder was added, and the mixture was stirred for 30min. The mixture was filtered, washed with anhydrous ethanol 3 times, washed with deionized water 3 times, and dried in a vacuum drying oven at 60°C for 24h to obtain modified graphene oxide;

[0061] A3. Add 5 g of cardanol, 3 g of 4-nitrophthalonitrile and 3.2 g of potassium carbonate to 10 g of dimethyl sulfoxide, stir at 180 rpm for 2 hours at 20 ° C, place in 25 mL of deionized water, stir for 30 minutes, stand for stratification, collect the upper liquid, repeat the steps of placing in 25 mL of deionized water, stirring for 30 minutes, standing for stratification and collecting the upper liquid for 3 times, and dry in an oven at 80 ° C for 4 hours to obtain a bio-based phthalonitrile resin;

[0062] A4, adding 3g of bio-based phthalonitrile resin and 0.3g of modified graphene oxide to 25mL of ethanol, stirring evenly, drying at 80°C to remove ethanol, heating to 230°C, pre-curing for 1 hour, hot pressing at 240°C and 10MPa for 2 hours, and cooling to room temperature to obtain a phthalonitrile resin mixture;

[0063] A5. Add 0.5 g of hydroxylated cellulose nanofibers to 80 mL of deionized water and stir to obtain a dispersion. Mix 8 g of the dispersion and 1 g of 1,2-bis(trimethoxysilyl)ethane and stir to obtain a dispersion. Add acetic acid to adjust the pH value to 3.5. Add 0.6 g of the phthalonitrile resin mixture and stir to react for 3 hours to form a gel. The gel is freeze-dried at -60°C and 1 Pa for 48 hours to obtain a high temperature resistant additive.

[0064] The thiol-terminated hyperbranched polymer is specifically prepared by the following steps:

[0065] 13 g of a hydroxyl-terminated hyperbranched polymer, 3 g of 3-mercaptopropionic acid, 0.2 g of p-toluenesulfonic acid and 35 mL of toluene were mixed and reacted at 110° C. for 10 h. After toluene was removed under reduced pressure, a thiol-terminated hyperbranched polymer was obtained.

[0066] Example 2

[0067] A highly heat-resistant water-based adhesive comprises the following raw materials in parts by weight: 50 parts of water-based epoxy resin, 18 parts of high-temperature resistant additives, 13 parts of thiol-terminated hyperbranched polymers, 1.5 parts of dodecanol ester, 0.7 parts of BYK111, 1.8 parts of BYK057, 4 parts of diethylenetriamine, and 20 parts of deionized water.

[0068] A method for preparing a highly heat-resistant water-based adhesive comprises the following steps:

[0069] S1. Mix 2 / 3 of deionized water, BYK111, BYK057 and diethylenetriamine, add dodecyl alcohol ester, and stir at 1000 rpm for 15 min to obtain a mixture;

[0070] S2. Mix the mixture, water-based epoxy resin, high temperature resistant additive, thiol-terminated hyperbranched polymer and remaining deionized water, and continue stirring at 1000 rpm for 8 minutes to obtain a water-based binder.

[0071] The high temperature resistant additive is specifically prepared by the following steps:

[0072] A1. Mix 3 g of kaolin, 0.6 g of sodium silicate, 0.2 g of phosphate and 2.5 g of starch, add to 20 mL of deionized water, stir evenly, dry in an oven at 170 ° C for 1 hour, grind to powder in a grinder, and pass through an 800-mesh sieve to obtain a composite powder;

[0073] A2, 0.2g of graphene oxide was added to 200mL of deionized water, ultrasonically treated at 40kHz for 60min, 0.03g of Tris-HCl with a pH of 7.5 was added, stirred evenly, 0.4g of dopamine was added, and the mixture was stirred and polymerized in a water bath at 60°C for 24 hours, 0.5g of the composite powder was added, stirred for 30min, filtered, washed 3 times with anhydrous ethanol, washed 3 times with deionized water, and dried in a vacuum drying oven at 60°C for 24h to obtain modified graphene oxide;

[0074] A3. Add 6 g of cardanol, 3.5 g of 4-nitrophthalonitrile and 3.3 g of potassium carbonate to 12 g of dimethyl sulfoxide, stir at 200 rpm for 2.5 hours at 25 ° C, place in 30 mL of deionized water, stir for 30 minutes, stand for stratification, collect the upper liquid, repeat the operation of placing in 30 mL of deionized water, stirring for 30 minutes, standing for stratification and collecting the upper liquid for 3 times, and dry in an oven at 80 ° C for 4 hours to obtain a bio-based phthalonitrile resin;

[0075] A4, adding 3.5g of bio-based phthalonitrile resin and 0.5g of modified graphene oxide to 30mL of ethanol, stirring evenly, drying at 80°C to remove ethanol, heating to 240°C, pre-curing for 2 hours, hot pressing at 240°C and 10MPa for 3 hours, and cooling to room temperature to obtain a phthalonitrile resin mixture;

[0076] A5. Add 1 g of hydroxylated cellulose nanofibers into 100 mL of deionized water and stir to obtain a dispersion. Mix 10 g of the dispersion and 2 g of a coupling agent and stir to obtain a dispersion. Add acetic acid to adjust the pH value to 4. Add 0.8 g of the phthalonitrile resin mixture and stir to react for 3 hours to form a gel. The gel is freeze-dried at -60°C and 1 Pa for 48 hours to obtain a high temperature resistant additive.

[0077] The thiol-terminated hyperbranched polymer is specifically prepared by the following steps:

[0078] 13.5 g of a hydroxyl-terminated hyperbranched polymer, 3.5 g of 3-mercaptopropionic acid, 0.3 g of p-toluenesulfonic acid and 40 mL of toluene were mixed and reacted at 120° C. for 12 h. After toluene was removed under reduced pressure, a thiol-terminated hyperbranched polymer was obtained.

[0079] Example 3

[0080] A highly heat-resistant water-based adhesive comprises the following raw materials in parts by weight: 60 parts of water-based epoxy resin, 20 parts of high-temperature resistant additives, 15 parts of thiol-terminated hyperbranched polymers, 2 parts of hexadecyl alcohol ester, 1 part of BYK065, 2 parts of BYK065, 4.5 parts of isophorone diamine, and 30 parts of deionized water.

[0081] A method for preparing a highly heat-resistant water-based adhesive comprises the following steps:

[0082] S1. Mix 2 / 3 parts of deionized water, BYK065, BYK065 and isophorone diamine, add hexadecanol ester, and stir at 1200 rpm for 20 min to obtain a mixture;

[0083] S2. Mix the mixture, water-based epoxy resin, high temperature resistant additive, thiol-terminated hyperbranched polymer and remaining deionized water, and continue stirring at 1200 rpm for 10 minutes to obtain a water-based binder.

[0084] The high temperature resistant additive is specifically prepared by the following steps:

[0085] A1. Mix 4 g kaolin, 0.7 g sodium silicate, 0.3 g phosphate and 3 g starch, add to 25 mL deionized water, stir evenly, dry in an oven at 180 ° C for 1 hour, grind to powder in a grinder, and pass through an 800 mesh sieve to obtain a composite powder;

[0086] A2, 0.3g of graphene oxide was added to 220mL of deionized water, ultrasonically treated at 40kHz for 60min, 0.04g of Tris-HCl with a pH of 8 was added, stirred evenly, 0.5g of dopamine was added, and the mixture was polymerized in a 65°C water bath for 25 hours, 0.7g of the composite powder was added, stirred for 30min, filtered, washed 3 times with anhydrous ethanol, washed 3 times with deionized water, and dried in a 60°C vacuum drying oven for 24h to obtain modified graphene oxide;

[0087] A3. Add 7 g of cardanol, 4 g of 4-nitrophthalonitrile and 3.4 g of potassium carbonate to 14 g of dimethyl sulfoxide, stir at 220 rpm for 3 hours at 30 ° C, place in 35 mL of deionized water, stir for 30 minutes, stand for stratification, collect the upper liquid, repeat the operation of placing in 35 mL of deionized water, stirring for 30 minutes, standing for stratification and collecting the upper liquid 3 times, and dry in an oven at 80 ° C for 4 hours to obtain a bio-based phthalonitrile resin;

[0088] A4, adding 4g of bio-based phthalonitrile resin and 0.7g of modified graphene oxide to 35mL of ethanol, stirring evenly, drying at 80°C to remove ethanol, heating to 250°C, pre-curing for 3 hours, hot pressing at 240°C and 10MPa for 4 hours, and cooling to room temperature to obtain a phthalonitrile resin mixture;

[0089] A5. Add 1.5 g of hydroxylated cellulose nanofibers to 120 mL of deionized water and stir to obtain a dispersion. Mix 12 g of the dispersion and 3 g of 1,2-bis(trimethoxysilyl)ethane and stir to obtain a dispersion. Add acetic acid to adjust the pH value to 4.5. Add 1 g of phthalonitrile resin to the mixture and stir to react for 3 hours to form a gel. The gel is freeze-dried at -60°C and 1 Pa for 48 hours to obtain a high temperature resistant additive.

[0090] The thiol-terminated hyperbranched polymer is specifically prepared by the following steps:

[0091] 14 g of a hydroxyl-terminated hyperbranched polymer, 4 g of 3-mercaptopropionic acid, 0.4 g of p-toluenesulfonic acid and 45 mL of toluene were mixed and reacted at 130° C. for 14 h. After toluene was removed under reduced pressure, a thiol-terminated hyperbranched polymer was obtained.

[0092] Comparative Example 1

[0093] A highly heat-resistant water-based adhesive comprises the following raw materials in parts by weight: 60 parts of water-based epoxy resin, 20 parts of high-temperature resistant additives, 15 parts of thiol-terminated hyperbranched polymers, 2 parts of hexadecyl alcohol ester, 1 part of BYK065, 2 parts of BYK065, 4.5 parts of isophorone diamine, and 30 parts of deionized water.

[0094] A method for preparing a highly heat-resistant water-based adhesive comprises the following steps:

[0095] S1. Mix 2 / 3 parts of deionized water, BYK065, BYK065 and isophorone diamine, add hexadecanol ester, and stir at 1200 rpm for 20 min to obtain a mixture;

[0096] S2. Mix the mixture, water-based epoxy resin, high temperature resistant additive, thiol-terminated hyperbranched polymer and remaining deionized water, and continue stirring at 1200 rpm for 10 minutes to obtain a water-based binder.

[0097] The high temperature resistant additive is specifically prepared by the following steps:

[0098] A1. Add 0.3 g of graphene oxide to 220 mL of deionized water, perform ultrasonic treatment at 40 kHz for 60 min, add 0.04 g of Tris-HCl with a pH of 8, stir evenly, add 0.5 g of dopamine, stir and polymerize in a 65 ° C water bath for 25 hours, stir for 30 minutes, filter, wash with anhydrous ethanol 3 times, wash with deionized water 3 times, and dry in a 60 ° C vacuum drying oven for 24 hours to obtain modified graphene oxide;

[0099] A2. Add 7 g of cardanol, 4 g of 4-nitrophthalonitrile and 3.4 g of potassium carbonate to 14 g of dimethyl sulfoxide, stir at 220 rpm for 3 hours at 30 ° C, place in 35 mL of deionized water, stir for 30 minutes, stand for stratification, collect the upper liquid, repeat the operation of placing in 35 mL of deionized water, stirring for 30 minutes, standing for stratification and collecting the upper liquid for 3 times, and dry in an oven at 80 ° C for 4 hours to obtain a bio-based phthalonitrile resin;

[0100] A3, adding 4g of bio-based phthalonitrile resin and 0.7g of modified graphene oxide to 35mL of ethanol, stirring evenly, drying at 80°C to remove ethanol, heating to 250°C, pre-curing for 3 hours, hot pressing at 240°C and 10MPa for 4 hours, cooling to room temperature, and obtaining a phthalonitrile resin mixture;

[0101] A4. Add 1.5 g of hydroxylated cellulose nanofibers to 120 mL of deionized water and stir to obtain a dispersion. Mix 12 g of the dispersion and 3 g of 1,2-bis(trimethoxysilyl)ethane and stir to obtain a dispersion. Add acetic acid to adjust the pH value to 4.5. Add 1 g of phthalonitrile resin to the mixture and stir to react for 3 hours to form a gel. The gel is freeze-dried at -60°C and 1 Pa for 48 hours to obtain a high temperature resistant additive.

[0102] The thiol-terminated hyperbranched polymer is specifically prepared by the following steps:

[0103] 14 g of a hydroxyl-terminated hyperbranched polymer, 4 g of 3-mercaptopropionic acid, 0.4 g of p-toluenesulfonic acid and 45 mL of toluene were mixed and reacted at 130° C. for 14 h. After toluene was removed under reduced pressure, a thiol-terminated hyperbranched polymer was obtained.

[0104] Comparative Example 2

[0105] A highly heat-resistant water-based adhesive comprises the following raw materials in parts by weight: 60 parts of water-based epoxy resin, 20 parts of high-temperature resistant additives, 15 parts of thiol-terminated hyperbranched polymers, 2 parts of hexadecyl alcohol ester, 1 part of BYK065, 2 parts of BYK065, 4.5 parts of isophorone diamine, and 30 parts of deionized water.

[0106] A method for preparing a highly heat-resistant water-based adhesive comprises the following steps:

[0107] S1. Mix 2 / 3 parts of deionized water, BYK065, BYK065 and isophorone diamine, add hexadecanol ester, and stir at 1200 rpm for 20 min to obtain a mixture;

[0108] S2. Mix the mixture, water-based epoxy resin, high temperature resistant additive, thiol-terminated hyperbranched polymer and remaining deionized water, and continue stirring at 1200 rpm for 10 minutes to obtain a water-based binder.

[0109] The high temperature resistant additive is specifically prepared by the following steps:

[0110] A1. Mix 4 g kaolin, 0.7 g sodium silicate, 0.3 g phosphate and 3 g starch, add to 25 mL deionized water, stir evenly, dry in an oven at 180 ° C for 1 hour, grind to powder in a grinder, and pass through an 800 mesh sieve to obtain a composite powder;

[0111] A2, 0.3g of graphene oxide was added to 220mL of deionized water, ultrasonically treated at 40kHz for 60min, 0.04g of Tris-HCl with a pH of 8 was added, stirred evenly, 0.5g of dopamine was added, and the mixture was polymerized in a 65°C water bath for 25 hours, 0.7g of the composite powder was added, stirred for 30min, filtered, washed 3 times with anhydrous ethanol, washed 3 times with deionized water, and dried in a 60°C vacuum drying oven for 24h to obtain modified graphene oxide;

[0112] A3. Add 1.5 g of hydroxylated cellulose nanofibers to 120 mL of deionized water and stir to obtain a dispersion. Mix 12 g of the dispersion and 3 g of 1,2-bis(trimethoxysilyl)ethane and stir to obtain a dispersion. Add acetic acid to adjust the pH value to 4.5. Add 1 g of modified graphene oxide and stir to react for 3 hours to form a gel. The gel is freeze-dried at -60°C and 1 Pa for 48 hours to obtain a high temperature resistant additive.

[0113] The thiol-terminated hyperbranched polymer is specifically prepared by the following steps:

[0114] 14 g of a hydroxyl-terminated hyperbranched polymer, 4 g of 3-mercaptopropionic acid, 0.4 g of p-toluenesulfonic acid and 45 mL of toluene were mixed and reacted at 130° C. for 14 h. After toluene was removed under reduced pressure, a thiol-terminated hyperbranched polymer was obtained.

[0115] Comparative Example 3

[0116] A highly heat-resistant water-based adhesive comprises the following raw materials in parts by weight: 60 parts of water-based epoxy resin, 20 parts of high-temperature resistant additives, 15 parts of thiol-terminated hyperbranched polymers, 2 parts of hexadecyl alcohol ester, 1 part of BYK065, 2 parts of BYK065, 4.5 parts of isophorone diamine, and 30 parts of deionized water.

[0117] A method for preparing a highly heat-resistant water-based adhesive comprises the following steps:

[0118] S1. Mix 2 / 3 parts of deionized water, BYK065, BYK065 and isophorone diamine, add hexadecanol ester, and stir at 1200 rpm for 20 min to obtain a mixture;

[0119] S2. Mix the mixture, water-based epoxy resin, high temperature resistant additive, thiol-terminated hyperbranched polymer and remaining deionized water, and continue stirring at 1200 rpm for 10 minutes to obtain a water-based binder.

[0120] The high temperature resistant additive is specifically prepared by the following steps:

[0121] A1. Mix 4 g kaolin, 0.7 g sodium silicate, 0.3 g phosphate and 3 g starch, add to 25 mL deionized water, stir evenly, dry in an oven at 180 ° C for 1 hour, grind to powder in a grinder, and pass through an 800 mesh sieve to obtain a composite powder;

[0122] A2, 0.3g of graphene oxide was added to 220mL of deionized water, ultrasonically treated at 40kHz for 60min, 0.04g of Tris-HCl with a pH of 8 was added, stirred evenly, 0.5g of dopamine was added, and the mixture was polymerized in a 65°C water bath for 25 hours, 0.7g of the composite powder was added, stirred for 30min, filtered, washed 3 times with anhydrous ethanol, washed 3 times with deionized water, and dried in a 60°C vacuum drying oven for 24h to obtain modified graphene oxide;

[0123] A3. Add 7 g of cardanol, 4 g of 4-nitrophthalonitrile and 3.4 g of potassium carbonate to 14 g of dimethyl sulfoxide, stir at 220 rpm for 3 hours at 30 ° C, place in 35 mL of deionized water, stir for 30 minutes, stand for stratification, collect the upper liquid, repeat the operation of placing in 35 mL of deionized water, stirring for 30 minutes, standing for stratification and collecting the upper liquid 3 times, and dry in an oven at 80 ° C for 4 hours to obtain a bio-based phthalonitrile resin;

[0124] A4. Add 4 g of bio-based phthalonitrile resin and 0.7 g of modified graphene oxide to 35 mL of ethanol, stir evenly, dry at 80 ° C to remove ethanol, heat to 250 ° C, pre-cure for 3 hours, hot press at 240 ° C and 10 MPa for 4 hours, and cool to room temperature to obtain a high temperature resistant additive.

[0125] The thiol-terminated hyperbranched polymer is specifically prepared by the following steps:

[0126] 14 g of a hydroxyl-terminated hyperbranched polymer, 4 g of 3-mercaptopropionic acid, 0.4 g of p-toluenesulfonic acid and 45 mL of toluene were mixed and reacted at 130° C. for 14 h. After toluene was removed under reduced pressure, a thiol-terminated hyperbranched polymer was obtained.

[0127] Comparative Example 4

[0128] A highly heat-resistant water-based adhesive comprises the following raw materials in parts by weight: 60 parts of water-based epoxy resin, 20 parts of high-temperature resistant additives, 15 parts of hydroxyl-terminated hyperbranched polymers, 2 parts of hexadecyl alcohol ester, 1 part of BYK065, 2 parts of BYK065, 4.5 parts of isophorone diamine, and 30 parts of deionized water.

[0129] A method for preparing a highly heat-resistant water-based adhesive comprises the following steps:

[0130] S1. Mix 2 / 3 parts of deionized water, BYK065, BYK065 and isophorone diamine, add hexadecanol ester, and stir at 1200 rpm for 20 min to obtain a mixture;

[0131] S2. Mix the mixture, water-based epoxy resin, high temperature resistant additive, hydroxyl-functionalized hyperbranched polymer and remaining deionized water, and continue stirring at 1200 rpm for 10 minutes to obtain a water-based binder.

[0132] The high temperature resistant additive is specifically prepared by the following steps:

[0133] A1. Mix 4 g kaolin, 0.7 g sodium silicate, 0.3 g phosphate and 3 g starch, add to 25 mL deionized water, stir evenly, dry in an oven at 180 ° C for 1 hour, grind to powder in a grinder, and pass through an 800 mesh sieve to obtain a composite powder;

[0134] A2, 0.3g of graphene oxide was added to 220mL of deionized water, ultrasonically treated at 40kHz for 60min, 0.04g of Tris-HCl with a pH of 8 was added, stirred evenly, 0.5g of dopamine was added, and the mixture was polymerized in a 65°C water bath for 25 hours, 0.7g of the composite powder was added, stirred for 30min, filtered, washed 3 times with anhydrous ethanol, washed 3 times with deionized water, and dried in a 60°C vacuum drying oven for 24h to obtain modified graphene oxide;

[0135] A3. Add 7 g of cardanol, 4 g of 4-nitrophthalonitrile and 3.4 g of potassium carbonate to 14 g of dimethyl sulfoxide, stir at 220 rpm for 3 hours at 30 ° C, place in 35 mL of deionized water, stir for 30 minutes, stand for stratification, collect the upper liquid, repeat the operation of placing in 35 mL of deionized water, stirring for 30 minutes, standing for stratification and collecting the upper liquid 3 times, and dry in an oven at 80 ° C for 4 hours to obtain a bio-based phthalonitrile resin;

[0136] A4, adding 4g of bio-based phthalonitrile resin and 0.7g of modified graphene oxide to 35mL of ethanol, stirring evenly, drying at 80°C to remove ethanol, heating to 250°C, pre-curing for 3 hours, hot pressing at 240°C and 10MPa for 4 hours, and cooling to room temperature to obtain a phthalonitrile resin mixture;

[0137] A5. Add 1.5 g of hydroxylated cellulose nanofibers to 120 mL of deionized water and stir to obtain a dispersion. Mix 12 g of the dispersion and 3 g of 1,2-bis(trimethoxysilyl)ethane and stir to obtain a dispersion. Add acetic acid to adjust the pH value to 4.5. Add 1 g of phthalonitrile resin to the mixture and stir to react for 3 hours to form a gel. The gel is freeze-dried at -60°C and 1 Pa for 48 hours to obtain a high temperature resistant additive.

[0138] The performance of the water-based adhesives prepared in Examples 1-3 and Comparative Examples 1-4 was tested.

[0139] Heat resistance test: The prepared water-based adhesive was placed in a thermogravimetric analyzer, the test atmosphere was nitrogen, the temperature was increased from 30 to 600°C, the temperature was increased at a rate of 10°C / min, the mass loss of the water-based adhesive was calculated, and the heat resistance temperature of the water-based adhesive was determined;

[0140] Mechanical property test: The water-based adhesive prepared above was applied to the battery surface, thermally bonded at 50°C, tested at a test speed of 1m / s, and the force on the pressure gauge was recorded to test the tensile strength at break and elongation at break of the water-based adhesive;

[0141] The peel strength of water-based adhesives was tested according to the national standard GB / T2790-1995;

[0142] The specific test results are shown in Table 1 below.

[0143] Table 1 Performance test of water-based binders prepared in Examples 1-3 and Comparative Examples 1-4

[0144] project Tensile strength at break / MPa Elongation at break / % Heat resistance / ℃ Peel strength (N / cm) Example 1 61.6 462 375 51.6 Example 2 62.3 468 381 52.3 Example 3 60.3 460 373 51.1 Comparative Example 1 45.6 412 306 50.6 Comparative Example 2 48.3 425 331 50.2 Comparative Example 3 49.6 435 344 50.1 Comparative Example 4 50.3 442 356 42.3

[0145] It can be seen from the data in Table 1 that the water-based binders prepared in Examples 1-3 have good heat resistance and mechanical properties. In Comparative Example 1, the modified graphene oxide prepared without adding the composite powder in step A2 is used to prepare a high temperature resistant additive and added to the water-based binder, and its heat resistance and mechanical properties decrease, proving that the kaolin in the composite powder can react with sodium silicate and phosphate at above 600°C, and can form an Al-O-Si three-dimensional skeleton and heat-resistant aluminum phosphate in the water-based binder, which has high high temperature resistance, and its three-dimensional skeleton structure can improve the mechanical resistance of graphene nanosheets. In Comparative Example 2, the phthalonitrile resin mixture is replaced with a high temperature resistant additive prepared by modified graphene oxide, and added to the aqueous binder, and its mechanical properties and heat resistance decrease, proving that the bio-based phthalonitrile resin, the long aliphatic chain contained therein has high toughness, and the bio-based phthalonitrile resin is attached to the surface of the modified graphene oxide, improving the dispersibility of the modified graphene oxide, avoiding agglomeration, and improving the heat resistance of the aqueous binder. In Comparative Example 3, the high temperature resistant additive prepared by hydroxylated cellulose nanofibers and coupling agents is not added, and is added to the aqueous binder, and its mechanical properties and heat resistance decrease, indicating that the cellulose aerogel has good compatibility with the aqueous binder matrix, so that the aerogel, that is, the high temperature resistant additive, acts better in the aqueous binder, enhancing the heat resistance and toughness of the aqueous binder. In Comparative Example 4, the thiol-terminated hyperbranched polymer was replaced with a hydroxyl-functionalized hyperbranched polymer and added to the aqueous adhesive. The peel strength decreased, proving that the thiol-terminated hyperbranched polyester can expand the free volume of the water-based epoxy resin, facilitate the movement of the epoxy resin molecular chain, and improve the toughness.

[0146] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0147] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A highly heat-resistant water-based adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of waterborne epoxy resin, 15-20 parts of high temperature resistant additive, 10-15 parts of thiol terminal hyperbranched polymer, 1-2 parts of film former, 0.5-1 parts of dispersant, 1.5-2 parts of defoamer, 3-4.5 parts of curing agent and 12-30 parts of deionized water; The high temperature resistant additive is obtained by mixing a phthalonitrile resin mixture, hydroxylated cellulose nanofibers, and a coupling agent; The phthalonitrile resin mixture is obtained by reacting 4-nitrophthalonitrile with cardanol and then mixing with modified graphene oxide; The modified graphene oxide is obtained by mixing and grinding kaolin, sodium silicate, phosphate and starch, and then depositing them on the surface of the graphene oxide; The high temperature resistant additive is specifically prepared by the following steps: A1. Mix kaolin, sodium silicate, phosphate and starch, add to deionized water, stir evenly, dry in an oven at 160-180°C for 0.5-1.5 hours, grind and sieve to obtain a composite powder; A2, adding graphene oxide to deionized water, ultrasonically treating, adding Tris-HCl, stirring evenly, adding dopamine, stirring and polymerizing in a water bath at 55-65°C for 23-25 ​​hours, adding composite powder, stirring, filtering, washing, and drying to obtain modified graphene oxide; A3, adding cardanol, 4-nitrophthalonitrile and potassium carbonate to dimethyl sulfoxide, stirring at 180-220 rpm for 2-3 hours at 20-30° C., placing in deionized water, stirring, standing and stratifying, collecting the upper liquid, repeating the operations of placing in deionized water, stirring, standing and stratifying and collecting the upper liquid, and drying to obtain a bio-based phthalonitrile resin; A4, adding bio-based phthalonitrile resin and modified graphene oxide to ethanol, stirring evenly, drying to remove ethanol, heating to 230-250° C., pre-curing for 1-3 hours, hot pressing, and cooling to room temperature to obtain a phthalonitrile resin mixture; A5, adding hydroxylated cellulose nanofibers to deionized water, stirring evenly to obtain a dispersion, mixing the dispersion and a coupling agent, stirring evenly, adding acetic acid to adjust the pH value to 3.5-4.5, adding the phthalonitrile resin mixture, stirring to form a gel, and freeze-drying the gel to obtain a high temperature resistant additive; The thiol-terminated hyperbranched polymer is obtained by reacting 3-mercaptopropionic acid with a hydroxyl-functionalized hyperbranched polymer; The thiol-terminated hyperbranched polymer is specifically prepared by the following steps: The hydroxyl-terminated hyperbranched polymer, 3-mercaptopropionic acid, p-toluenesulfonic acid and toluene are mixed, reacted at 110-130° C. for 10-14 hours, and toluene is removed under reduced pressure to obtain a thiol-terminated hyperbranched polymer.

2. A highly heat-resistant water-based adhesive according to claim 1, characterized in that: In step A1, the ratio of kaolin, sodium silicate, phosphate, starch and deionized water is (2-4) g: (0.5-0.7) g: (0.1-0.3) g: (2-3) g: (15-25) mL; In step A2, the amount ratio of graphene oxide, deionized water, Tris-HCl, dopamine, and composite powder is (0.1-0.3) g: (180-220) mL: (0.02-0.04) g: (0.3-0.5) g: (0.3-0.7) g.

3. A highly heat-resistant water-based adhesive according to claim 1, characterized in that: In the step A3, the amount ratio of the cardanol, 4-nitrophthalonitrile, potassium carbonate, dimethyl sulfoxide, and deionized water is (5-7) g: (3-4) g: (3.2-3.4) g: (10-14) g: (25-35) mL; In step A4, the ratio of the bio-based phthalonitrile resin, modified graphene oxide, and ethanol is (3-4) g: (0.3-0.7) g: (25-35) mL.

4. A highly heat-resistant water-based adhesive according to claim 1, characterized in that: In step A5, the ratio of the hydroxylated cellulose nanofibers to deionized water is (0.5-1.5) g: (80-120) mL; In step A5, the mass ratio of the dispersion, coupling agent and phthalonitrile resin mixture is (8-12):(1-3):(0.6-1).

5. A highly heat-resistant water-based adhesive according to claim 1, characterized in that: The amount ratio of the hydroxyl-terminated hyperbranched polymer, 3-mercaptopropionic acid, p-toluenesulfonic acid and toluene is (13-14) g: (3-4) g: (0.2-0.4) g: (35-45) mL.

6. A highly heat-resistant water-based adhesive according to claim 1, characterized in that: The epoxy equivalent of the waterborne epoxy resin is 800-1400; the defoamer is at least one of BYK022, BYK057, BYK065, and BYK1765; and the dispersant is at least one of BYK104 and BYK111.

7. A highly heat-resistant water-based adhesive according to claim 1, characterized in that: The film-forming agent includes any one of benzyl alcohol, phenylethyl alcohol, dodecanol ester, hexadecanol ester, ethylene glycol butyl ether, ethylene glycol butyl ether acetate, and butylene glycol butyl ether acetate; the curing agent is selected from any one of phenolic amine, diethylenetriamine, isophoronediamine, and N-cyanoethyldiethylenetriamine.

8. A method for preparing the highly heat-resistant water-based adhesive according to any one of claims 1 to 7, comprising the following steps: S1. Mix 2 / 3 parts of deionized water, dispersant, defoamer and curing agent, add film-forming agent, and stir at 800-1200 rpm for 10-20 min to obtain a mixture; S2. Mix the mixture, water-based epoxy resin, high temperature resistant additive, thiol-terminated hyperbranched polymer and remaining deionized water, and continue stirring at 1000-1200 rpm for 5-10 minutes to obtain a water-based binder.

Citation Information

Patent Citations

  • Use of highly branched polymers in polymer dispersions for gloss colours

    CN101868509A

  • Cardanol modified nitrile-based phenolic resin adhesive and preparation method thereof

    CN110105905A